2012
DOI: 10.3892/ijo.2012.1439
|View full text |Cite
|
Sign up to set email alerts
|

Influence of resistance to 5-fluorouracil and tomudex on [18F]‑FDG incorporation, glucose transport and hexokinase activity

Abstract: incorporation is influenced by resistance to antifolate and fluoropyrimidine-based anti-cancer drugs in a drug-dependent manner and the underlying mechanisms appear to be cell-and drug-dependent. Glucose transport may be a useful marker of resistance to 5FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cancer cells escaped 5-FU-induced cell death by entering a quiescent state during cell cycle progression (42). Previous studies have demonstrated that high rates of glucose uptake caused a reduction in 5-FU-induced cytotoxicity (43, 44). Moreover, chemicals that modulate glucose metabolism, such as 3-bromopyruvate, iodoacetate, dichloroacetate, and 2-deoxyglucose, also sensitized cancer cells to 5-FU (45, 46).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells escaped 5-FU-induced cell death by entering a quiescent state during cell cycle progression (42). Previous studies have demonstrated that high rates of glucose uptake caused a reduction in 5-FU-induced cytotoxicity (43, 44). Moreover, chemicals that modulate glucose metabolism, such as 3-bromopyruvate, iodoacetate, dichloroacetate, and 2-deoxyglucose, also sensitized cancer cells to 5-FU (45, 46).…”
Section: Introductionmentioning
confidence: 99%